A cross-sectional study of Malaysian low-income drug addict wives: relationship between family impact, coping and mental wellbeing - Adnan, Haikal Anuar; Arshat, Zarinah; Ahmad Shahril, Nurul Saidatus Shaja’ah (F1000 Research, 2022)
Background: The involvement of the husbands in the issue of drug addiction has impacted the wives’ livelihoods. Due to drug addiction amongst husbands, the wives experience stress and strain. The Stress Strain Coping Support Model (SSCS) was established to better comprehend how coping influences stress and strain. Thus, the purpose of this study was to determine the relationship between the stress which refers to family impact experienced by the wives of drug addicts, in terms of economic difficulties and marital conflict, and mental wellbeing. Furthermore, this study examines the role of coping as a mediating factor between family impact and mental wellbeing. Methods: This study involved 132 wives of low-income drug addicts in Malaysia, who were selected using a purposive sampling method. Economic Strain Scale (ESS) and Braiker-Kelly Marital Conflict Scale (BKMCS) were used to measure family impact. Coping and Adaptation Processing Scale Short Form (CAPS-SF) and Short Warwick-Edinburgh Mental Wellbeing Scale (SWEMWBS) were used to measure coping and mental wellbeing of the respective respondents. Results: Path analysis using SmartPLS software version 3.3.7 showed that there is a direct association between family impact and coping, and between coping and mental wellbeing. The results also showed that family impact was associated indirectly with mental wellbeing through coping. Conclusions: The findings benefited drug addict wives and practitioners related to this field in terms of enhancing the use of coping mechanisms in managing family impact and improving mental wellbeing, specifically amongst low-income drug addict wives.